Air Conditioner (AC) Operation Using the Internet of Things - I Nyoman Sukarma; Beauregard Anakottapary; I Gede Ketut Sri Budarsa; I Ketut Parti (Jurnal Penelitian Pendidikan IPA, 2025)
Create an Internet of Things-based Air Conditioner operating system to make it easier to operate the AC. This research examines whether the system designed can transmit IR Code via IR Transmitter to AC if the device is placed at different distances. The steps to make it happen are to follow the stages of the prototyping method, which consist of gathering requirements, developing prototypes, and testing prototypes. The hardware circuit built consists of the Node MCU ESP8266, DHT 11 sensor, Infra-Red, software consisting of Arduino IDE, and blynk. By placing the NodeMCU ESP 8266 in positions with different distances, the tool can send IR Code data via the IR Transmitter to the AC, buttons on the blynk application have been made and can work according to their functions. The test was carried out with 4 different location positions, namely position 1 with a distance of 1 meter, position 2 with a distance of 3 meters, position 3 with a distance of 2 meters, and position 4 with a distance of 4 meters. From 4 test location positions with sufficient category signals to very good categories, microcontrollers can be connected to the blynk application on smartphone users. The Blynk application can function according to the commands made, the IR code can be sent through the IR transmitter to the air conditioner (AC). The DHT 11 sensor successfully measures the temperature and humidity of the air. Hopefully, in the future, the development of this tool into a multi-controller capable control not only AC but also other electronic devices.